Incidence, Morbidity Pattern and Outcomes among Preterm Babies Admitted in Special Newborn Care Unit: A Retrospective Observational Study from Nellore, Andhra Pradesh, India - Nerella Jwala Vasavi; Sandhyadevi Lingala; Suresh Reddeppagari; Nanaji Rao Pala (Indian Journal of Neonatal Medicine and Research)
Introduction: Neonatal mortality and morbidity remain a significant challenge in India, accounting for 24% of global neonatal mortality. Special Newborn Care Units (SNCUs) have been established to address this issue. Therefore, it is important to evaluate the outcomes of SNCUs by measuring morbidity patterns and hospital stays among preterm neonates in these units. Aim: To evaluate the incidence, morbidity patterns and outcomes of preterm neonates admitted to the SNCU. Materials and Methods: This was a retrospective observational study conducted at ACSR Government Medical College, Nellore, Andhra Pradesh, India, from January 2020 to December 2022, during which 4,135 neonatal admissions were analysed. The study included all preterm newborns admitted to the SNCU. Additionally, only live births were included to ensure consistency in data analysis. The variables studied included gender, prematurity, birth weight, twin gestations, inborn/outborn status, outcomes in terms of mortality and morbidity, and complications. The Chi-square test was used for analysing differences in proportions. R esults: Out of 4,135 neonates, 1,559 (37.7%) were preterm, with annual variations of (494/1,461) 33.8% in 2020, increasing to (542/1,322) 41% in 2021, before slightly decreasing to (523/1,352) 38.7% in 2022. Among the preterm neonates, 809 (51.9%) were males and 750 (48.1%) were females. Early preterm births (≤32 weeks’ gestation) constituted 69% (1,076) of the cases, while late preterm births accounted for 31% (483). Co-morbidities included Respiratory Distress Syndrome (RDS) 1,141 (73.2%), Low Birth Weight (LBW) 637 (40.9%), and birth asphyxia 139 (8.9%). C onclusion: There was a relatively high incidence of preterm births in the SNCU. Mortality was observed to be notably higher among outborn neonates compared to inborn neonates, particularly due to RDS and sepsis. The study underscores the significant burden of preterm births in Nellore, highlighting the need for enhanced perinatal care, early referral systems and targeted interventions to mitigate neonatal morbidity and mortality in this region.